미세다륜침을 이용한 인삼추출물의 피부개선 효과연구 - 구진숙; Jin Suk Koo (大韓本草學會誌, 2021)
Objectives : The purpose of this study was to find out the efficacy of ginseng on the skin by comparing the difference effect between only MTS (microneedle therapy system) and the ginseng solution application after MTS treatment. Methods : The present author performed once a week and total 3 times of MTS treatment. The treatment time took about 5~10 minutes and the depth of the needle was adjusted according to the participant's skin condition. In the control group, skin toner was applied after MTS and in the experimental group, ginseng extract dissolved toner was applied. One week after each treatment, the change of skin condition was measured. Two weeks after the end of the clinical trial, the skin condition was checked again. Results : In the case of t-zone oil, there was a significant decrease in the test group and in the case of pores and pigmentation, there was a significant decrease in both the test group and the control group, but the degree of significance was greater in the test group. In the case of skin tone, there was an increase, but no significance. Conclusion : The MTS treatment itself showed good effects on t-zone oil, pores, pigmentation, and skin tone. But the effect was much better when the ginseng extract solution was applied to the skin after MTS treatment. This study suggests that ginseng solution increases the efficacy of MTS.